Odd harmonious labeling on the union of flower graphs - Firmansah, Fery; Tasari, Tasari; Sungkono, Joko (Desimal: Jurnal Matematika, 2024)
Applications of graph labeling in the fields of communication network addressing, database management, secret sharing schemes, and cryptology. Graphs that satisfy the odd harmonious labeling property are called odd harmonious graphs. The purposes of the research are to obtain the construction of the union of zinnia flower graphs, the union of double quadrilateral flower graphs, the rosella flower graphs, and the union of rosella flower graphs. The research method consists of literature study, graph class construction, graph labeling construction, theorem construction, and proof. The result of the research proves that the union of the zinnia flower graph, the double quadrilateral flower graph, the rosella flower graph, and the union of the rosella flower graph satisfies the odd harmonious labeling property. Thus, the novelty of this research is that the properties of the new graph class of odd harmonious graphs are obtained.